Gualitative Indicators for Measuring the Performance Development of selected Cities - Mavrič, Jasmina; Tominc, Polona; Bobek, Vito (Naše gospodarstvo/Our economy, 2014)
Recognizing that cities are becoming generators of economic development and a source of growth for the national economy, researchers are increasingly identifying the stages of development and positioning of cities upon which the adequate pre- paration of strategic and development guidelines is dependent. The comparison of the level of their development efficiency calls for indicators measuring the perfor- mance of cities that are representative and comparable between countries. In the case of medium-sized cities, we consequently have to question the applicability of the methodology and indicators used mostly in cases of large, global cities by inter- nationally recognized institutions. With the established set of qualitative indicators and assistance from a computer program for multiparameter decision-making pro- cesses (DEXi), this paper also seeks to compare the performance development of selected European cities.